National strategic plan for the conservation and use of priority crop wild relatives in Zambia - Bioversity International; University of Birmingham; Zambia Agriculture Research Institute (2016)
The leaflet provides a summary of the major results achieved in Zambia within the project: In Situ Conservation and Use of Crop Wild Relatives in three ACP countries of the Southern African Development Community (SADC) region (2014 - 2016), in particular about the priority CWR and the identification of in situ conservation sites.